The use of volcanic beach sand as a pseudo-invariant target for atmospheric correction using Landsat images - Chrysoulakis, Nektarios; Themistocleous, Kyriacos; Retalis, Adrianos; Hadjimitsis, Diofantos G. (My University, 2012)
Pseudo-invariant targets are often used for atmospheric correction, as their reflectance values are stable across time. Sand is often used as a pseudo-invariant target, although there is conflicting research about its effectiveness as a pseudo invariant target. This study will examine the effectiveness of volcanic sand as a pseudo-invariant target. The study area is a 250x250 meter area of volcanic beach sand near Limassol, Cyprus. In-situ spectroradiometric measurements were taken using field spectrometers to obtain the reflectance values of volcanic sand over wet and dry conditions. The varying saturation levels of the sand due to rainfall, humidity and high temperatures was considered. A series of Landsat-5 TM and Landsat-7 ETM satellite imagery were atmospherically corrected using the darkest pixel method in order to assess the effectiveness of the volcanic sand as a pseudo-invariant target. The mean in-situ in-band reflectance values as found from the ground measurements were compared with the at-satellite reflectance values following atmospheric correction. It was found that precipitation conditions such as rainfall affected the reflectance values of sand. The study found that wet sand had a significantly lower reflectance value compared to dry sand. Further, salinization also affected the reflectance value of volcanic sand. Therefore, precipitation conditions need to be considered when using sand as a non-variant target for atmospheric correction. 2012 SPIE.
Keywords: Atmospheric humidity; Beaches; Optical radar; Pixels; Precipitation(chemical); Rain; Reflection; Remote sensing; Satellite imagery; Volcanoes; Atmospheric corrections; Calibration targets; Ground measurements; Pixel methods; Pseudo-invariant targets; Reflectance values; Spectroradiometric measurements; Volcanic sand; Sand